(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the context of globalization of global economy and intense competition and steady increase in population, mortality rates among people with infectious and parasitic diseases are increasing. International organizations are also paying much attention to fighting these problems and their consequences. In particular, the UN Sustainable Development Program up to 2030 emphasizes “issues related to the elimination of immunodeficiency, tuberculosis and malaria epidemics in the period up to 2030, as well as measures to combat hepatitis and other waterborne infections”. Successful implementation of these tasks requires stabilization of nosocheological and nosogeographic situations in arid climates. Medical geographical situation in the regions is one of the most important factors determining the development of society and the way of life of the population. Addressing medical geographical problems and improving public health, reducing morbidity and increasing life expectancy are of vital scientific and practical importance.